Stakeholder Visions for Biodiversity Conservation in Developing Countries - Adenle, Ademola; Stevens, Casey; Bridgewater, Peter (Sustainability, 2015)
The 2014 Conference of the Parties (COP 12) for the Convention on Biological Diversity (CBD) was another step on the road to achieving the Aichi Targets the CBD agreed in 2010. It was also a key step on the way to making progress towards the vision of a more balanced relationship between people and the rest of biodiversity by 2050. Many key issues were left for this COP by negotiators from COP 11 and earlier meetings; such as settling financial issues, articulating clearly the Aichi Targets for national implementation by 2020, or providing clear guidance on capacity-building for developing states. This paper utilizes 22 stakeholder interviews taken at the 2012 Hyderabad COP to develop discussion of ongoing issues in the CBD negotiations. These interviews yielded a number of tractable policy opportunities available for the 2014 Conference to create significant space for developing countries to contribute effectively to global achievement of the Aichi Targets. Breakthroughs and developments at the COP, despite the inevitability of some difficult discussions, will be provided by developing country perspectives. Despite that potential traction, Ministers at the high-level segment noted that progress towards the Aichi targets is insufficient and recognizing there was still much to do on resource mobilization, reaffirmed their commitment to mobilize financial resources from all sources for the effective implementation of the Strategic Plan for Biodiversity 2011–2020. As we enter the second half of the 2011–2020 decade, developing countries must be placed at the center of efforts to improve sustainable use, conservation and benefit sharing of biodiversity around the world.